Utility optimization-based bandwidth allocation for elastic and inelastic services in peer-to-peer networks - Li, Shiyong; Zhang, Yue; Wang, Yan; Sun, Wei (Zielona Góra: Uniwersytet Zielonogórski)
This paper considers reasonable bandwidth allocation for multiclass services in peer-to-peer (P2P) networks, measures the satisfaction of each peer as a customer by a utility function when acquiring one service, and develops an optimization model for bandwidth allocation with the objective of utility maximization. Elastic services with concave utilities are first considered and the exact expression of optimal bandwidth allocation for each peer is deduced.
Keywords: P2P networks; bandwidth allocation; elastic and inelastic services; utility function